2021
DOI: 10.5267/j.msl.2021.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting employee performance: The case of government employees in Oman

Abstract: There is a universal consensus that improving employee performance is a cornerstone for any organization’s path to success and prosperity. However, when it comes to identifying what factors trigger such an improvement, there is anything but consensus among researchers. In this paper, a sample of government employees in the Sultanate of Oman is studied to discern the factors that affect employee performance. A factor analysis is applied to validate the constructs used to measure the various variables. A correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In this study, the JD of Oman's public sector is examined. JD in this sector can explain the civil servant's responsibility and what is expected of them [40]. Completing an accurate JD is an essential first step in the selection process.…”
Section: Job Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the JD of Oman's public sector is examined. JD in this sector can explain the civil servant's responsibility and what is expected of them [40]. Completing an accurate JD is an essential first step in the selection process.…”
Section: Job Descriptionmentioning
confidence: 99%
“…One of Oman 2040's stated goals is to improve government workers' skill sets and output [23]. This is because the country needs to maximize EP in order to effectively manage ever-decreasing available resources as a result of falling oil earnings and rising competition for available jobs among its own citizens [24]. Many public sector workers in Oman are leaving for the private sector because they feel their workload, pay, and advancement chances are not being fairly distributed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by during COVID-19 concluded that the employee performance of government employees in Oman is reduced during the pandemic (Saadouli & Al-Khanbashi, 2021;Sulaiman et al, 2020). There is no official data from Ministry of Education on employee performance during COVID-19 but it expects that like other government employees the performance is also reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediating Effect of Leadership Style in Relationship of Employee Motivation towards Employee Performance for Production Media in Oman to provide work as a social welfare mechanism is becoming increasingly difficult as a result of diminishing oil revenues and a significant growth in the national labour force (Saadouli & Al-Khanbashi, 2021;Saadouli & Al-Khanbashi, 2020). According to an Oman study, employees who are unable to obtain the necessary learning process for them to grow and learn new things are more likely to leave the firm in search of a better one.…”
mentioning
confidence: 99%